2021
DOI: 10.1111/liv.15051
|View full text |Cite
|
Sign up to set email alerts
|

Lung and lymph node metastases from hepatocellular carcinoma: Comparison of pathological aspects

Abstract: Background & Aims: Extrahepatic metastasis from hepatocellular carcinoma (HCC) is a catastrophic event, yet organ-specific pathological characteristics of metastatic HCC remain unclear. We aimed to characterize the pathological aspects of HCC metastases to various organs. Methods:We collected intrahepatic HCC (cohort 1, n = 322) and extrahepatic metastatic HCC (cohort 2, n = 130) samples. Clinicopathological evaluation and immunostaining for K19, CD34, αSMA, fibroblast-associated protein (FAP), CAIX, VEGF, PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…In addition, the authors reported decreasing responses to nivolumab in the order of intrahepatic tumors (ORR, 10.1%) followed by metastatic tumors in the lung (ORR, 24.2%) and LN (ORR, 37.1%). The above results are supported by a previous study demonstrating that sites of HCC metastasis have altered pathological features [228] and Tregs have distinctive functions through different mediators in other organs [229].…”
Section: Disease Status and Tumor Burdensupporting
confidence: 85%
“…In addition, the authors reported decreasing responses to nivolumab in the order of intrahepatic tumors (ORR, 10.1%) followed by metastatic tumors in the lung (ORR, 24.2%) and LN (ORR, 37.1%). The above results are supported by a previous study demonstrating that sites of HCC metastasis have altered pathological features [228] and Tregs have distinctive functions through different mediators in other organs [229].…”
Section: Disease Status and Tumor Burdensupporting
confidence: 85%
“…However, patients with sinonasal metastasis had a dismal prognosis and they all died within one to nine months. Overall, the prognosis of patients with HCC with distant metastasis is poor, and the clinicopathologic characteristics and the survival of metastatic HCC varied according to various metastatic organs (22). Zhan et al founded that lung metastasis has a worse prognosis than bone metastasis, and the average survival time of brain metastasis is shorter than bone or lung metastasis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Extrahepatic metastasis is a main reason for the poor prognosis of HCC and the lungs and bone are the main target organs of HCC metastasis (Zhang et al, 2021;Woo et al, 2022). According to the "seed and soil" theory, the metastatic target organ provides a favorable microenvironment for the extravasation, colonization and growth of the circulating tumor cells, including increase of vascular permeability, Frontiers in Pharmacology frontiersin.org local inflammation and immunosuppression (de Groot et al, 2017).…”
Section: Formation Of the Pre-metastatic Nichementioning
confidence: 99%